Research on hydrodynamic suspension nanoscale polishing for K9 optical glass. (1st October 2007) - Zhao, J.; Cao, Z.Q.; Zhan, J.M.; Zhang, F.; , L. Niu
In this paper, a hydrodynamic suspension nanoscale polishing system based on Computer Numerical Control (CNC) is established. A new type of compliant polishing tool system is developed, which can realise nanoscale displacement compensating. Also polishing experiments on K9 optical glass, using the polishing fluid mixed with nanoscale SiC abrasive particles, have been conducted to investigate the fundamental machining mechanism. A high-quality surface without crystallite dislocation and micro cracks is achieved. It is shown that the removal of atomic layers size can be done by colliding nanoscale abrasive particles with the workpiece surface.